Design and Build Chatbot Application for Tourism Object Information in Bengkulu City - Rohman, M. Abdul; Subarkah, Pungkas (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2024)
As technology develops and the number of new arrivals to the city of Bengkulu increases, the need for information regarding information related to tourism in Bengkulu is also increasing. The growth of Bengkulu tourism increases very rapidly every year as many local and foreign tourists visit the city of Bengkulu. Therefore, the author intends to build a chatbot that functions as a Virtual Assistant for Bengkulu tourists and those outside the city of Bengkulu. This chatbot is able to provide information to tourists through data stored in the system. The implementation and design of this software produces a chatbot that is built using the Extreme Programming (XP) method. Chatbots are also able to answer questions according to the abilities embedded in them. The application of chatbots provides fast information in a relatively short time to obtain information because the questions asked can be answered directly.